Implementasi Penerapan MDA pada Game Endless Runner 2D CAVE RACER Berbasis Android - Muhammad Fahrullazi; Riwinoto Riwinoto; Sarah Emilla Hutapea (Politeknik Negeri Batam, 2019)
In today's rapidly expanding technology this game can be enjoyed across a wide range of platforms from PCS, tablets to smartphones. One of the approaches to making games is the design of games using the MDA method. The MDA method is Mechanics, Dynamics and Aesthetics. In this method, designing a game is done from the perspective of the designer, which is from the definition of Aesthetics, determination of the game Dynamics and Mechanic. The measurement of this approach is to use a successful model and fail from Aesthetics performed through the survey process in 50 respondents. Research is a study of how MDA's modeling implementation is in the development of a game. This developed Game is titled Cave Racer with endless runner genre. Authors develop this game because games with this genre are much appreciated among the community both children, teenagers and adults because the game is easy to play and simple enough that the road continues and dodge from the obstacles. This game is based on Android, this game is genre endless runner and developed using Unity. The game aesthetics used are Challenge and Submission. The Dynamics games used are 7 and there are 8 Mechanics. Measuring model succes and models indicates Aesthetics the game from 50 respondents showed Aesthetics the challenge tends to be successful which is reaching 79.6% and Aesthetics submission also success reaches 82%. Keyword : game, MDA, Endless Runner